3D morphometry aids facial analysis of individuals with a childhood cancer. Issue 11 (2nd August 2016) - Hopman, Saskia M. J.; Merks, Johannes H. M.; Suttie, Michael; Hennekam, Raoul C. M.; Hammond, Peter
Abstract : A group of patients who had cancer as a child were previously found to have distinct patterns of morphological abnormalities. In this study, we investigated the added value of 3D shape analysis to characterize their facial morphology. Primarily, we showed in an objective and quantitative manner that the overall facial dysmorphism of the individuals who had had a childhood cancer was significantly greater than that of the controls. We also demonstrated how the same approach can be used to detect a similar disparity for a more localized malar region comprising customized disconnected patches defined on both sides of the face. In addition, by comparing original face surfaces to their mirrored forms, we confirmed that the patient group had significantly greater facial asymmetry than the controls. Each of these results made use of surface shape differences not detectable by simple linear or angular characteristics as might be used in analyses based on measures captured manually or derived from landmarks annotating 2D photographic images. We conclude that 3D morphometric analysis of a relatively small heterogeneous patient group can further delineate face shape differences from typically developing individuals that are too subtle or geometrically complex to identify or quantify objectively with conventional clinical and anthropometric approaches. © 2016 Wiley Periodicals, Inc.